Alterações comportamentais e cognitivas em ratos expostos às crises epilépticas intrauterinas - Novaes, Gisane Faria (2010)
It is well established that exposure to teratogenic agents, like valproic acid, increase the risk of developing autism spectrum disorders. Considering that epileptic pregnant woman use antiepileptic therapy, it makes difficult to search evidences whether the epilepsy per se, when uncontrolled, produce alterations on offspring or whether the medication associated with the genetic predisposition are the factor responsible for these alterations. Animal models are useful once variables can be controlled. This study evaluated the behavior of offspring exposed to maternal convulsive seizures in utero. An experimental model of temporal lobe epilepsy was induced in female wistar by pilocarpine administration (350 mg/kg). Control animals received saline injection. After the occurrence of spontaneous seizure, the rats were mated and seizure frequency was recorded (6h/day) during the pregnancy. Early after birth, rat pups from epileptic and control dams were cross-fostered with a control dams. The third group pups born from control dams were maintained with their own mother. Number of pups per litter from epileptic dams was significantly reduced, and malformations were present in 15% of them. The animal behaviors were analyzed from postnatal days 60. Offspring from epileptic dam showed deficit in social interaction and cognition, with no changes in anxiety, suggesting that epileptic seizures during pregnancy is harmful to fetal developing. Furthers studies are need for a broader assessment of animal behavior repertoire across the life span, independently the seizures during pregnancy to be or not a risk factor for developing of autism spectrum disorder.